Micro-finance and Women Empowerment - Sharma, Puspa Raj (Journal of Nepalese Business Studies, 2008)
This paper examines the effects of women’s participation in group-based micro-credit pro-grams on a large set of qualitative responses to questions that characterize women’s autonomy and gender relations within the household. The data come from a special survey carried out in hill and tarai in 2004-2006 of Nepal. The results are consistent with the view that women’s participation in micro-credit programs helps to increase women’s empowerment. Credit program participation leads to women taking a greater role in household decision-making, having greater access to financial and economic resources, having greater social networks, having greater bargaining power compared with their husbands, and having greater freedom of mobility. Female credit also tended to increase spousal communication in general about family planning and parenting concerns. Ecologically, the higher impact on women’s empowerment was noticed in terai. The reason may be relatively lower social and economic status of terai women at the time of program initiation compared to that of hills. As a result, even a small change in their status would get reflected distinctly.The Journal of Nepalese Business Studies Vol. IV, No. 1 (2007) pp. 16-27